Anticipating missing reference standard data when planning diagnostic accuracy studies. (9th February 2016) - Naaktgeboren, Christiana A; de Groot, Joris A H; Rutjes, Anne W S; Bossuyt, Patrick M M; Reitsma, Johannes B; Moons, Karel G M
Abstract : Results obtained using a reference standard may be missing for some participants in diagnostic accuracy studies. This paper looks at methods for dealing with such missing data when designing or conducting a prospective diagnostic accuracy study